EFFECT OF SUPPLEMENTATION OF DETOXIFIED MATRI FLOUR WITH WHEAT FLOUR ON THE QUALITY OF pAN BREAD (Biological Sciences - PJSIR, 2003)
Breads were prepared from wheat flour supplemented with  5, 10, 15, 20 and 25% of detoxified  matri  flour and evaluated for sensory acceptability, i.e. bread taste, aroma, texture, crumb  colour, grain, loaf volume,  crust colour, symmetry of  form, character of crust and  evenness of bake. Brabender  farinograph,  mixograph  and  viscoarnylograph  characteristics of flour were also studied. Farinograph water absorption, arrival time and dough development time increased and dough stability decreased and amylograph peak viscosities, mixograph peak height and mixing time decreased as level of supplementation with matri flour increased. The quantities  of crude  protein,  crude  fibre, crude  fat  and  ash  increased with the increase of matri flour in wheat flour. Increasing levefs of legume substitution decreased many  sensory  parameters of wheat  bread. Results  indicate that detoxified  matri  flour can  successfully be  substituted  for wheat  flour  in  breads  at levels  up to  10% . Legume  substitution  tended  to increase the protein  level  in  the finished product.